Effectiveness and quality evaluation of electrical stunning versus chilling in Norway lobsters (Nephrops norvegicus) - Albalat, Amaya; Gornik, Sebastian G.; Muangnapoh, Chonchanok; Neil, Douglas M. (Food control, 2022)
In the last decade, public interest in the welfare of decapod crustaceans has increased in many parts of the world. This has led to changes in legislation on methods for slaughter in a number of countries, while in others pressure for regulation changes is growing. Electro-stunning may have the potential for reducing noxious stimuli experienced by crustaceans during slaughter. However, data on activity in the central nervous system (CNS) and product quality-related data (indicative of consumer acceptability) are not available for most of the important decapod crustaceans, including the commercially valuable Norway lobster, Nephrops norvegicus. In this study, recordings of nerve activity showed that electro-stunning can render N. norvegicus rapidly insensible qualifying it as a potential humane slaughter procedure. In contrast, placing lobsters on ice for 30 min did not suppress neural activity. In terms of subsequent shelf life, results at day 7 based on QIM, total bacteria counts, H2S-producing bacteria, muscle pH, TMA and biogenic amines indicate no significant differences between the methods of stunning. From a quality perspective, electro-stunning did shorten the period that the product would be considered fresh (higher K-values up to day 5) and triggered faster melanosis development in the cephalothorax, an effect possibly linked to the increased temperature recorded in this area due to the imposed electrical current. However, no significant differences were detected on the cooked products by a trained sensory taste panel. While shelf life is not affected by the electro-stunning process, care should nevertheless be taken to avoid melanosis development, and the consumer perception of freshness in electro-stunned product should be studied further.
Gesehen am 29.07.2022